Rock-Hosted Subsurface Biofilms: Mineral Selectivity Drives Hotspots for Intraterrestrial Life - Casar, Caitlin P.; Kruger, Brittany R.; Osburn, Magdalena R. (Frontiers in Microbiology, 2021)
The continental deep subsurface is likely the largest reservoir of biofilm-based microbial biomass on Earth, but the role of mineral selectivity in regulating its distribution and diversity is unclear. Minerals can produce hotspots for intraterrestrial life by locally enhancing biofilm biomass. Metabolic transformations of minerals by subsurface biofilms may occur widely with the potential to significantly impact subsurface biogeochemical cycles. However, the degree of impact depends upon the amount of biofilm biomass and its relationship to host rock mineralogy, estimates that are currently loosely constrained to nonexistent. Here, we use in situ cultivation of biofilms on native rocks and coupled microscopy/spectroscopy to constrain mineral selectivity by biofilms in a deep continental subsurface setting: the Deep Mine Microbial Observatory (DeMMO). Through hotspot analysis and spatial modeling approaches we find that mineral distributions, particularly those putatively metabolized by microbes, indeed drive biofilm distribution at DeMMO, and that bioleaching of pyrite may be a volumetrically important process influencing fluid geochemistry at this site when considered at the kilometer scale. Given the ubiquity of iron and sulfur-bearing minerals at this site and globally, and the amount of biomass they can support, we posit that rock-hosted biofilms likely contribute significantly to subsurface biogeochemical cycles. As more data becomes available, future efforts to estimate biomass in the continental subsurface should incorporate host rock mineralogy.